2000
DOI: 10.1083/jcb.150.3.499
|View full text |Cite
|
Sign up to set email alerts
|

A Kinesin-Related Protein, Krp180, Positions Prometaphase Spindle Poles during Early Sea Urchin Embryonic Cell Division

Abstract: We have investigated the intracellular roles of an Xklp2-related kinesin motor, KRP180, in positioning spindle poles during early sea urchin embryonic cell division using quantitative, real-time analysis. Immunolocalization reveals that KRP180 concentrates on microtubules in the central spindle, but is absent from centrosomes. Microinjection of inhibitory antibodies and dominant negative constructs suggest that KRP180 is not required for the initial separation of spindle poles, but instead functions to transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
26
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
8
26
0
Order By: Relevance
“…In Drosophila, KLP61F is sequestered in the nucleus during prophase and does not participate in the initial separation of the spindle poles, but only following nuclear envelope breakdown can KLP61F interact with MTs and exert forces that push apart the poles (18,19). Our data on sea urchin embryonic cells is consistent with the hypothesis that in this system, KRP 170 associates with cytoplasmic MTs where it interacts with MTs to help push apart the centrosomes during initial spindle assembly and anaphase spindle elongation, so that inhibiting its function leads to prophase or anaphase arrest (6).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In Drosophila, KLP61F is sequestered in the nucleus during prophase and does not participate in the initial separation of the spindle poles, but only following nuclear envelope breakdown can KLP61F interact with MTs and exert forces that push apart the poles (18,19). Our data on sea urchin embryonic cells is consistent with the hypothesis that in this system, KRP 170 associates with cytoplasmic MTs where it interacts with MTs to help push apart the centrosomes during initial spindle assembly and anaphase spindle elongation, so that inhibiting its function leads to prophase or anaphase arrest (6).…”
Section: Discussionsupporting
confidence: 77%
“…How KRP 110 and KRP 170 may work in concert with other mitotic motors, including kinesin C (25), KRP 180 (6), and cytoplasmic dynein are topics for future work.…”
Section: Discussionmentioning
confidence: 99%
“…During anaphase, KLP-18 staining also concentrated between the separating groups of chromosomes, with a dim zone at the spindle equator (Figure 2A). These patterns are similar to those seen for Xklp2 in mitotic Xenopus cultured cells and KRP 180 in mitotic sea urchin embryos (Boleti et al, 1996;Rogers et al, 2000), although a dim zone at the anaphase equator has not been reported previously.After cytokinesis, KLP-18 accumulated somewhat around the nucleus and at the cortex near sites of cell-cell contact ( Figure 2B). During later stages of embryogenesis, KLP-18 levels gradually diminished in somatic cells but increased in the primordial germ cells Z2 and Z3, presumably due to expression in the embryonic germ line (Figure 2, C-E).…”
supporting
confidence: 67%
“…Also, amino acids 507-510 (SPAR) in this "stalk" region provide a potential cdc2 kinase phosphorylation site ([T/S]PX[K/R]; Nigg, 1993). These features are similar to those of the stalk regions of other members of the Klp2 subfamily (Boleti et al, 1996;Wittmann et al, 1998;Rogers et al, 2000).Database searches revealed that ϳ750 kb away from klp-18 in the C. elegans genome is a pair of predicted ORFs (C33H5.4 and C33H5.3) with high sequence similarity to the KLP-18 amino acid sequence. The C33H5.4 ORF, previously designated as klp-10 (Siddiqui, 2002), is separated from C33H5.3 by only 19 base pairs of genomic DNA.…”
mentioning
confidence: 61%
See 1 more Smart Citation